Comparison of 6-Month and Prolonged Dual Antiplatelet Therapy after Percutaneous Coronary Intervention with Biodegradable Polymer Everolimus-Eluting Stent - Yong-Hoon Yoon; Gyung-Min Park; Jae-Hyung Roh; Sung-Ho Her; Seong-Hoon Lim; Tae Soo Kang; Seung Jin Lee; Jang-Whan Bae; WoongGil Choi; Yong-Mo Yang; Junghee Kim; Yu Jeong Choi; et al. (Cardiology Research and Practice)
Background. The optimal duration of dual antiplatelet therapy (DAPT) after biodegradable-polymer (BP) everolimus-eluting stent (EES) implantation remains uncertain. Methods. This study analyzed 793 patients who underwent percutaneous coronary intervention (PCI) with BP-EES in 10 cardiovascular centers in Korea between July 2016 and January 2018. Using the prescription data at 6 months post-PCI, we divided these patients into two groups, namely, short-DAPT and prolonged-DAPT groups, which underwent DAPT for 6 and > 6 months of PCI, respectively. The primary endpoint, which included mortality, myocardial infarction, or target-vessel revascularization at 2 years, was compared by propensity score (PS) matching between the two groups. Results. Out of the 793 patients, 283 matched pairs were identified by PS matching. Out of this matched population, 405 (71.6%) patients had an acute coronary syndrome. The primary endpoint did not differ in 2 years between the short-DAPT and prolonged-DAPT groups (7.5% vs. 8.3%; hazard ratio, 0.87; 95% confidential interval, 0.47–1.60; P=0.648). Likewise, no difference was found regarding mortality, cardiac mortality, myocardial infarction, target-lesion failure, target-vessel failure, and bleeding events defined by the Bleeding Academic Research Consortium and Thrombolysis In the Myocardial Infarction classification. Meanwhile, one patient in the short-DAPT group had definite stent thrombosis at 364 days post-PCI. Subgroup analysis showed that several anatomical and procedural factors were not significantly related to DAPT duration. Most patients (77.4%) in both groups were prescribed clopidogrel at discharge. Conclusions. In real-world patients undergoing PCI with BP-EES, the ischemic and bleeding endpoints demonstrated no difference between 6-month and prolonged (>6 months) DAPT.